Ocean Data Product Integration Through Innovation-The Next Level of Data Interoperability - Buck, Justin J. H.; Bainbridge, Scott J.; Burger, Eugene F.; Kraberg, Alexandra C.; Casari, Matthew; Casey, Kenneth S.; Darroch, Louise; Rio, Joaquin Del; Metfies, Katja; Delory, Eric; Fischer, Philipp F.; Gardner, Thomas; et al. (Frontiers in Marine Science, 2019)
In the next decade the pressures on ocean systems and the communities that rely on them will increase as multiple stressors of climate change, food security and human activities start to impact. Our ability to manage and sustain our oceans will depend on the data we collect and the information and knowledge generated. Much of the uptake of this knowledge will be outside the ocean domain, for example by policy makers, local Governments, custodians and other organizations, so it is imperative that we democratize or open the access and use of ocean data. This paper looks at how technologies, scoped by standards, best practice and communities of practice, can be deployed to change the way that ocean data is accessed, utilized, value added and transformed into information and knowledge. The current portal-download model which requires the user to know what data exists, where it is stored, in what format and with what processing, limits the uptake and use of ocean data. Using examples from a range of disciplines, a web services model of data and information flows is presented. A framework is described, including the systems, processes and human components, which delivers a radical rethink about the delivery of knowledge from ocean data. A series of vision statements describe parts of the future vision along with a series of recommendations about how this may be achieved. The paper recommends the development of virtual test-beds for end to end development of new data workflows and knowledge pathways. This supports the continued development, rationalization and uptake of standards, creates a platform around which a community of practice can be developed, promotes cross discipline engagement from ocean science through to ocean policy, allows for the commercial sector, including the informatics sector, to partner in delivering outcomes and provides a focus to leverage long term sustained funding. The next ten years will be ‘make or break’ for many ocean systems. The decadal challenge is to develop the governance and co-operative mechanisms to harness emerging information technology to deliver on the goal of generating the information and knowledge required to sustain oceans into the future.